Multiple mechanisms contribute to the development of clinically significant azole resistance in Aspergillus fumigatus - Moye-Rowley, W. S. (Frontiers in Microbiology, 2015)
Infections caused by the filamentous fungus Aspergillus fumigatus are a significant clinical issue and represent the second most-common form of fungal infection. Azole drugs are effective against this pathogen but resistant isolates are being found more frequently. Infections associated with azole resistant A. fumigatus have a significantly increased mortality making understanding drug resistance in this organism a priority. The target of azole drugs is the lanosterol α-14 demethylase enzyme encoded by the cyp51A gene in A. fumigatus. Mutations in cyp51A have been described that give rise to azole resistance and been argued to be the primary, if not sole, contributor to azole resistance. Here, I discuss recent developments that indicate expression of ATP-binding cassette (ABC) transporter proteins are also key participants in azole resistance. ABC transporters are well-established determinants of drug resistance in other fungal pathogens and seem likely to play a similar role in A. fumigatus.